New and Emerging Tobacco Products and the Nicotine Endgame: The Role of Robust Regulation and Comprehensive Tobacco Control and Prevention. Issue 19 (7th May 2019) - Bhatnagar, Aruni; Whitsel, Laurie P.; Blaha, Michael J.; Huffman, Mark D.; Krishan-Sarin, Suchitra; Maa, John; Rigotti, Nancy; Robertson, Rose Marie; Warner, John J.
Abstract : The advent of new tobacco products such as electronic cigarettes and the dramatic rise in their use, especially by adolescents and young adults, are significant public health concerns. Electronic cigarettes have become the most popular tobacco products for youth and adolescents in the United States and are attracting youth to new avenues for nicotine addiction. Although these products may have benefit by helping some smokers quit or to move to a less harmful product, the long-term health effects of these products and the net public health effect associated with their use remain unclear and widely debated. There is increasing concern that the use of newer tobacco products may catalyze transition to the use of other tobacco products or recreational drugs, particularly in young adults. Therefore, there is urgent need for robust US Food and Drug Administration regulation of all tobacco products to avoid the significant economic and population health consequences of continued tobacco use. Although the American Heart Association acknowledges that the ultimate endgame would be an end to all tobacco and nicotine addiction in the United States, it supports first minimizing the use of all combustible tobacco products while ensuring that other products do not addict the next generation of youth and adolescents. The endgame strategy needs to be coordinated with the long-standing, evidence-based tobacco control strategies that have significantly reduced tobacco use and initiation in the United States.